2017
DOI: 10.1681/asn.2016080828
|View full text |Cite
|
Sign up to set email alerts
|

Association between Soluble Klotho and Change in Kidney Function: The Health Aging and Body Composition Study

Abstract: CKD appears to be a condition of soluble klotho deficiency. Despite known associations between low soluble klotho levels and conditions that promote kidney damage, such as oxidative stress and fibrosis, little information exists regarding the longitudinal association between soluble klotho levels and change in kidney function. We assayed serum soluble -klotho in 2496 participants within the Health Aging and Body Composition study, a cohort of older adults. The associations between soluble klotho levels and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 49 publications
(62 reference statements)
5
76
0
1
Order By: Relevance
“…Although a direct association between the plasma level of soluble αKlotho and tubular expression of αKlotho protein was not clearly determined, higher expression of soluble αKlotho is associated with less pathological evidence of aging, such as kidney fibrosis and systemic markers of oxidative stress [34, 35], which indicated the kidney protective effect of αKlotho [36]. In clinical reports, decreases in plasma levels of soluble αKlotho were independently associated with arterial stiffness [37], early chronic kidney disease [38], and a higher risk of decline in kidney function [39] in a non-chronic kidney disease population. These reports indicate that the plasma level of soluble αKlotho is a good biomarker for tubular cell senescence, even in living kidney donors who have sufficient kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Although a direct association between the plasma level of soluble αKlotho and tubular expression of αKlotho protein was not clearly determined, higher expression of soluble αKlotho is associated with less pathological evidence of aging, such as kidney fibrosis and systemic markers of oxidative stress [34, 35], which indicated the kidney protective effect of αKlotho [36]. In clinical reports, decreases in plasma levels of soluble αKlotho were independently associated with arterial stiffness [37], early chronic kidney disease [38], and a higher risk of decline in kidney function [39] in a non-chronic kidney disease population. These reports indicate that the plasma level of soluble αKlotho is a good biomarker for tubular cell senescence, even in living kidney donors who have sufficient kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that Klotho may exert a multitude of actions to mitigate the activation of intrarenal RAS as well as systemic aldosterone production. Overall, strong evidence demonstrates the suppression of renal Klotho expression in diabetic renal disease, and more vigorous functional studies are needed to define the renoprotective action of this antiaging protein as well as its relationship with intrarenal RAS [30][31][32][33][34][35].…”
Section: Klotho-vitamin D-vdr Axismentioning
confidence: 99%
“…It has been shown that Klotho deficiency turns the kidney prone to damage from oxidative stress, ischemia and inflammation, whereas its supplementation (in acute as well as chronic settings) attenuates fibrosis-related kidney diseases 30,31 . Circulating Klotho is decreased in mouse models of diabetes and in patients in early stages of CKD, even in the absence of GFR loss, and it could be further related to a higher risk of eGFR decline 32,33 . In the most recent meta-analysis that considered eight prospective studies (although just two studies were carried out on diabetes 34,35 , it was found that decreased Klotho levels were associated with increased adverse kidney outcomes, which indicated that Klotho could be a prognostic biomarker for patients with CKD 36 .…”
Section: Human Studies Of Protective Factors For Renal Function Lossmentioning
confidence: 99%